(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Uzbek children’s games are an important part of national folklore and cultural heritage. They reflect the traditions, customs, moral values, and social life of the Uzbek people. Through games, children learn cooperation, respect, bravery, honesty, and national identity. This article analyzes the reflection of national culture and traditional characteristics in Uzbek children’s games. The study is based on folklore materials, cultural analysis, and comparative observations. The results show that Uzbek traditional games preserve national values and serve as an educational tool for younger generations.